Akuarium Neighborhood Plays The Eviction - Achmad Firas Khudi (Proceedings Series on Social Sciences & Humanities, 2023)
The Jakarta government evicted an urban community of Akuarium in 2016, which caused socio-economic and immaterial difficulties. Yet, violent eviction instigated a kind of play in the community. A theory of urban play envisages how the community responds and utilizes failed development projects drawing from the practices of graffiti, car jockeys, and navigation of traffic jams. The research method includes field and internet ethnography. The research uncovers precarious life in the community due to existing poverty and the incident of eviction. Their poverty informs a structural problem of low income. The eviction exacerbates the condition with the erasure of the economy, housing, and cultural life, leading to a repressed mental state among them. Akuarium people enact an urban play as a small tactic responding to various kinds of violence and the difficulty of eviction in the function of survival.